Combinação de métodos computacionais e da ciência cidadã para o mapeamento de áreas suscetíveis a inundações: estudo de caso em Campina do Monte Alegre - SP - Cilto, Gabriela Gonçalves (Universidade Federal de São Carlos, 2025)
The lack of systematization of hydrological data is a common issue in Brazil. One indication of this is that only 40.6% of municipalities possess a risk management plan, a crucial step in mitigating the impacts of natural disasters. Furthermore, the effects of climate change have intensified the frequency of extreme events, thereby increasing the need for methodologies that more accurately reflect reality, are easily obtainable, and accessible for predicting and mitigating the impacts of such events. In light of this scenario, the present study aimed to map flooded areas resulting from extreme events based on a historical retrospective of flood occurrences using citizen science, and to compare the flood maps generated by different methods. To this end, two Digital Terrain Models (DTMs) were employed: one generated by a drone without RTK and another provided by ANADEM. Additionally, two methods for generating flood maps were evaluated: the HAND Model software and QGIS using the table reclassification tool. Regarding the results obtained, the ANADEM DTM combined with the HAND Model demonstrated superior performance, achieving an AG of 100% and an F1 score of 1.00 for the 2004 event. For the year 2016, this configuration yielded an AG of 85.71% and an F1 score of 0.92. The maps generated using the drone DTM produced less representative results, with AG values of 69.23% and 61.54% for the year 2004, and AG of 85.71% and F1 score of 0.92 for the 2016 event using the HAND and QGIS models, respectively. Despite the limitations associated with the method, the collection of data and flood records through citizen science proved to be an effective alternative for obtaining information in regions with a deficit of systematized data. The integration of this approach with the analysis of historical series enabled the mapping of flood-prone areas and the identification of critical events, a fundamental step in the development of risk management plans. It is concluded that the applied methodology constitutes a viable, accessible, and reproducible alternative for mapping areas susceptible to flooding, thereby contributing to the enhancement of territorial management and the strengthening of public policies focused on adaptation and mitigation in response to natural disasters.
Combining computational methods and citizen science for mapping flood susceptible areas: a case study in Campina do Monte Alegre - SP
Keywords: Inundações; Geoprocessamento; Sócio-hidrologia; Floods; Geoprocessing; Sociohydrology; ENGENHARIAS::ENGENHARIA CIVIL::ENGENHARIA HIDRAULICA::HIDROLOGIA; 11. Cidades e Comunidades Sustentáveis; 13. Ação contra a Mudança Global do Clima